English Teachers’ Beliefs in Autonomy Learning in Senior High School At Northern of Lima Puluh Kota Regency - Rahmalia, Indah; Nifriza, Ifna (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Beliefs (understanding) are something that consciously or unconsciously influences a person's habits. Therefore, Beliefs influence what a person says, means and does. So, Beliefs will have an impact on the teacher's treatment in teaching. Especially in developing autonomy (independence) in students. This research includes descriptive qualitative research. Participants in this research were teachers at SMK N 1 Kec. Luak and SMA N 1 Kec. Lareh Sago Halaban 2016/2017 academic year. There are 4 (four) teachers at SMK N 1 Kec. Luak and there are 3 (three) teachers at SMA N 1 Kec. Lareh Sago Halaban. The author uses a questionnaire as a data source. There are 24 items in the questionnaire. Questionnaires were analyzed using a Likert scale. Based on the results of the Likert scale, the author uses an interval formula to find the score of the teacher's understanding of independent learning. The results of this research describe English teachers' understanding of learning. First, overall English teachers do not have enough confidence that independent learning can be implemented well in their schools. Second, English teachers lack understanding of the definition of independence. Third, English teachers have very little understanding of the role of teachers, students and teaching materials in teaching children to be independent. Fourth, teachers really believe their students can be responsible for their learning. Fifth, English teachers do not understand how to develop students' independence. Keywords: Autonomy Learning, Belief, Fostering Autonomy, Responsibility Teacher Belief